People's Republic of China-Hong Kong Special Administrative Region : Financial System Stability Assessment-Press Release and Statement by the Executive Director for the People's Republic of China-Hong Kong Special Administrative Region. (IMF Staff Country Reports; Country Report ;, 2021)
The main macro-financial risks relate to extensive linkages to Mainland China, stretched real estate valuations, and exposure to shifts in global market and domestic risk sentiment, compounded by escalating U.S.-China tensions. Stress tests show that the financial system is resilient to severe macro-financial shocks, but there are pockets of vulnerabilities in foreign bank branches, investment funds, households, and nonfinancial corporates. Hong Kong SAR's financial sector is also exposed to physical and transition risks from climate change.